2009
DOI: 10.1152/ajpheart.00503.2009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological stimulation of soluble guanylate cyclase modulates hypoxia-inducible factor-1α in rat heart

Abstract: . Pharmacological stimulation of soluble guanylate cyclase modulates hypoxia-inducible factor-1␣ in rat heart. Am J Physiol Heart Circ Physiol 297: H1274 -H1280, 2009. First published August 14, 2009 doi:10.1152/ajpheart.00503.2009.-Mechanical load and ischemia induce a series of adaptive physiological responses by activating the expression of O 2-regulated genes, such as hypoxia inducible factor-1␣ (HIF-1␣). The aim of this study was to explore the interaction between HIF-1␣ and soluble guanylate cyclase (sG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Given that sGC modulation and hypoxia-inducible factor may both modulate hemoglobin concentrations, this has become a focus of new therapies for patients with renal disease. [14][15][16] Finally, it is possible that vericiguat plays a role in red blood cell senescence, 16,17 resulting in a small decline in circulating red blood cells (without affecting other blood lines) and leading to no effect on the clinical outcomes by simple clearance of aged red blood cells. Some strengths and limitations warrant consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Given that sGC modulation and hypoxia-inducible factor may both modulate hemoglobin concentrations, this has become a focus of new therapies for patients with renal disease. [14][15][16] Finally, it is possible that vericiguat plays a role in red blood cell senescence, 16,17 resulting in a small decline in circulating red blood cells (without affecting other blood lines) and leading to no effect on the clinical outcomes by simple clearance of aged red blood cells. Some strengths and limitations warrant consideration.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with previous studies [30][31][32] showing that NO via cGMP production prevents hypoxia-mediated acquisition of malignant phenotypes in tumour cells and suggest that modulation of HIF-1α may be an important aspect of the mechanism by which NO/cGMP signalling regulates hypoxic responses. Although many of the studies examining the regulatory effects of NO on HIF-1α accumulation and/or HIF-1 activity have proposed cGMP-independent mechanisms of HIF-1 regulation, Tsuruda et al [37] have found that activation of sGC/cGMP signalling in cultured cardiomyocytes decreased hypoxia-induced HIF-1α protein accumulation; this further supports the notion that the cGMPdependent signalling interferes with hypoxic induction of HIF-1α accumulation and suggests that such mechanism of HIF-1α modulation may apply to a variety of normal and transformed cells.…”
Section: Discussionmentioning
confidence: 99%